Supporting Fisheries Management With Genomic Tools: A Case Study of Kingklip (Genypterus capensis) Off Southern Africa - Schulze, Melissa J.; von der Heyden, Sophie; Japp, David; Singh, Larvika; Durholtz, Deon; Kapula, Veronica K.; Ndjaula, Hilkka O. N.; Henriques, Romina (Frontiers in Marine Science, 2020)
Kingklip, Genypterus capensis, is one of southern Africa’s most valuable demersal fisheries resources, with a wide geographic distribution spanning South Africa and Namibia. Previous studies have provided evidence for multiple stocks in South Africa, but the extent of stock structuring across the Southern African region remains unclear. In this study we genotyped over 40 000 SNPs to characterise the spatial distribution of genomic variation for G. capensis throughout its core distribution. Results suggest that fish sampled at the northernmost range (off central Namibia) are characterised by the lower genomic diversity, although the region was characterised by the highest number of private SNPs, suggesting some degree of geographic isolation. Using neutral and putative outlier loci independently, we show that Kingklip exhibits three population clusters, “northern Benguela”, “southern Benguela” and South African “South Coast”. Population differentiation was observed only using “outlier” loci, suggesting that local adaptation might be one of the main drivers of the observed differentiation. Overall, our research provides novel insights into the regional dynamics that can support the sustainable long-term exploitation of this valuable fisheries resource.